EFFECTIVENESS OF PESTICIDE TANK MIXTURES AGAINST PESTS AND DISEASES IN TECHNOLOGY OF WINTER WHEAT CULTIVATION IN THE NORTHERN STEPPE OF UKRAINE - Pysarenko, P. V.; Matiukha, V. L.; Pysarenko, P. P.; Antonenko, Ya. V. (Scientific Progress & Innovations, 2021)
One of the reasons for the decrease in grain yield of winter wheat besides weed infestation is spreading and developing of diseases and pests during its cultivation. The processes of strengthening or weakening the resistance of winter wheat to damage by pests and diseases, in modern arable farming of the steppe zone, are significantly influenced by the general level of farming culture and integrated plant protection system, one of which are modern plant protection products. Restricting the spreading of diseases and pests with plant protection means is another important agricultural measure, the effectiveness of which depends on the correct choice of insecticides and fungicides from a wide range of preparations and compliance with regula-tions for their maximum impact on pests without polluting the environment. The level of damage by all types of pests and diseases of winter wheat was generally low and 15–20 times lower than the economic threshold of harmfulness (ETH) for all harmful objects, while the ETH for Swedish fly (Oscinella) is 10–15 larvae per m², ground beetle (Zabrus tenebrioides) up to 2–3 pcs/m², and pentatomid eurygaster (Eurygaster integ-riceps Put.) – 5–6 pcs/m². ETH of septoria disease (Septoria tritici Rob. et Desm.) makes 5 % of the affected wheat area, powdery mildew (Erysiphe graminis (DC) – 10–15 %, Fusarium wilt disease (Fusarium gra-minearum Schwabe, Fusarium culmorum) – also10–15 % of infected plants, etc. The maximum effectiveness in combatting diseases of winter wheat plants is ensured by tank mixtures of preparations of Falcon fungi-cide (0.6 l/ha) with herbicides and of Tytul Duo fungicide (0.2 l/ha) with herbicides, which resulted in almost complete neutralization (100 %) of various diseases. The combination of Falcon (0.6 l/ha) and Tytul Duo (0.2 l/ha) fungicides with Monitor (20 g/ha) and Prymadona (0.8 l/ha) herbicides improved the effectiveness of the fungicides. After all, areas free from weeds have a higher resistance to diseases due to better aeration of plant stand, lower air humidity, and as a result, worse conditions for the development of diseases. The highest effectiveness in pest control is provided by Kinfos insecticide-acaricide (0.35 l/ha) in combination with the new generation herbicide Prymadona (0.8 l/ha), which ensures almost 100 % destruction of pests. The comparison of control variant data without plant protection means together with application of insecti-cide, acaricide and fungicide tank mixtures with herbicides proves the complete necessity of using the above mentioned insecticides in combatting pests and diseases of winter wheat areas.